Antimicrobial Agents alters the In Vitro Plant Regeneration in Solanum nigrum (L.) - C.V. Naidu2*, T.M. Sridhar1 and (Journal of Phytology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Effect of different antimicrobial agents such as bavistin, cefotoxime and kanamycin on shoot regeneration using auxillary bud explnts of Solanum nigrum was studied. Axillary buds when cultured on MS medium supplemented with bavistin (200 mg/L) and in combination with BA (1.0 mg/L) showed the formation of multiple shoot was 4.5 and 4.8 respectively.Ã‚Â  Bavistin in combination with cytokinins showed enhanced shoot formation from the explants. Cefotoxime does not decrease the shooting response but it induced the maximum shoot formation (3.5) with a high frequency of regeneration (88%) from the axillary bud cultures of Solanum nigrum.The influence of kanamycin on regeneration of Solanum nigrum was evaluated.MS medium supplemented with 50 <span style="font-size: 10pt; font-family: Symbol; mso-ascii-font-family: 'Arial Narrow'; mso-hansi-font-family: 'Arial Narrow'; mso-char-type: symbol; mso-symbol-font-family: Symbol; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">m<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">M/L kanamycin induced highest number of shoots (3.0) and highest mean shoot regeneration (90%).